PHYTOCHEMICAL SCREENING AND CHARACTERIZATION OF VOLATILE COMPOUNDS BY GAS CHROMATOGRAPHY-MASS SPECTROMETRY FROM “NEPHROLEPIS EXALTATA” - SHARMA, DEEPAK KUMAR; RS, DAVE; KR, SHAH (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Plants contain various types of phytochemicals with different solvent as per solvation properties, depending on their polarity. The goal of this analysis is to compare the effects of different solvents on the phytochemical profile and the characterization of different volatile bioactive compounds of Nephrolepis exaltata, a typical fern belonging to pteridophyte species. Methods: For the screening of phytochemical, a sequential extraction was carried out using different solvent systems namely methanol (MeOH), chloroform, carbon tetrachloride, hexane, and ethyl acetate (EtAc). A varied range of phytochemicals was found in the extracts. The volatile components were analyzed using the hyphenated technique gas chromatography-mass spectrometry (GC-MS). Results: All the extracts were found to be rich in alkaloids, whereas phenols and Phytosterols were extracted only in MeOH. The MeOH extract of the fern presented positive results for six phytochemical tests and the n-Hexane (nH) extract presented positive results for seven phytochemical tests. The present investigation on the plant N. exaltata aimed to prove that pteridophytes should have various kinds of bioactive phytochemicals and the selection of solvent for extraction of phytochemicals should be based on the target compounds. Conclusion: From the % yield of different extract, it can be concluded that some the bioactive phytochemicals are more soluble in more polar solvents such as MeOH, some are soluble in moderate solvents like EtAc and mostly non-polar organic molecules can be extracted using non-polar solvents like nH. The GC-MS characterization indicates the presence of different fatty compounds and sterols in the plant extract.